1990
DOI: 10.1084/jem.171.1.315
|View full text |Cite
|
Sign up to set email alerts
|

B cells are required for induction of T cell abnormalities in a murine retrovirus-induced immunodeficiency syndrome.

Abstract: A retrovirus-induced immunodeficiency syndrome of mice (1-4), termed MAIDS, shares many features with HIV induced disease in man (5) . Studies of host-virus interactions contributing to the pathogenesis of this syndrome showed that abnormalities ofB cells, including polyclonal activation and impaired responses to mitogenic and specific antigenic stimuli, are dependent on the presence of activated T cells (6) of CD4 + phenotype (7) . Cells contributing to CD4' T cell activation under normal conditions include M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
69
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 19 publications
(21 reference statements)
1
69
0
Order By: Relevance
“…Although the presence of B cells and B cell-T cell interactions have been shown to be critical for development of MAIDS (11,12,41,42), little is known about functional features of B cells that would favor or inhibit MAIDS progression. Possible candidates for affecting MAIDS development are the B cell surface molecules CD19 and associated CR2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the presence of B cells and B cell-T cell interactions have been shown to be critical for development of MAIDS (11,12,41,42), little is known about functional features of B cells that would favor or inhibit MAIDS progression. Possible candidates for affecting MAIDS development are the B cell surface molecules CD19 and associated CR2.…”
Section: Discussionmentioning
confidence: 99%
“…However, in mixed virus inoculation, infection of B cells is required for efficient infection of T cells and macrophages, because animals lacking functional mature B cells are resistant to MAIDS (11,12). This conclusion was based on studies in mice depleted of B cells from birth by administration of a rabbit Ab to IgM or mice with a B cell deficiency due to a targeted mutation of the membrane exon of the IgM H chain gene.…”
mentioning
confidence: 99%
“…Animals depleted or devoid of B cells are also resistant to MAIDS (10,13). MHC class II knockout (KO) animals, which lack CD4 ϩ T cells, are also resistant to disease (14).…”
mentioning
confidence: 99%
“…Previous studies of mice with MAIDS demonstrated that interactions between CD4+ T cells and B cells are central to the pathogenesis of this syndrome; infected mice depleted in vivo of CD4+ T cells had phenotypically and functionally normal B cells [8], while infected mice depleted of mature B cells had phenotypically and functionally normal CD4+ and CD8+ T cells [9]. Indirect evidence suggests that B cell-de-pendent T cell activation through a mechanism involving a retrovirus-associated superantigen is crucial to the development of the disease [10].…”
mentioning
confidence: 99%
“…The disorder has a natural history in many ways comparable to human immunodeficiency virus (HIV-l )-induced AIDS in humans and has therefore been termed murine AIDS (MAIDS) [3]. Dysfunction of CD4+ T cells is a key feature in both conditions and precedes a numerical reduction of this T cell subset even though the LP-BM5 viruses have no selective tropism for CD4+ T cells [7].Previous studies of mice with MAIDS demonstrated that interactions between CD4+ T cells and B cells are central to the pathogenesis of this syndrome; infected mice depleted in vivo of CD4+ T cells had phenotypically and functionally normal B cells [8], while infected mice depleted of mature B cells had phenotypically and functionally normal CD4+ and CD8+ T cells [9]. Indirect evidence suggests that B cell-de-…”
mentioning
confidence: 99%